The Mitochondrial Markers Provide New Insights Into the Population Demographic History of Coilia nasus With Two Ecotypes (Anadromous and Freshwater) - Gao, Tianxiang; Ying, Yiping; Yang, Qiaoli; Song, Na; Xiao, Yongshuang (Frontiers in Marine Science, 2020)
The Pleistocene climate oscillations have been proven to have profound influences in the evolutionary processes of marine species and left significantly tractable footprints in genomes of marine fauna. However, such history remains unknown for the Japanese grenadier anchovy Coilia nasus, a relatively large fish found in marine, freshwater and brackish water. In order to provide insight into the phylogeographic pattern and historical demography of C. nasus, we employed the mtDNA D-loop and Cyt b as molecular markers to estimate the genetic variation among populations of C. nasus. We took samples from 18 populations throughout the distribution of C. nasus. Partial sequences of mtDNA D-loop (n = 424) and Cyt b (n = 129) were obtained. Four phylogeographic lineages were revealed by the mtDNA D-loop analysis. Frequency changes of the four lineages throughout the species’ distribution indicated limited genetic exchange among three major geographic regions. Patterns of isolation-by-distance were detected among the populations. Neutrality test, mismatch distribution, and network analyses consistently showed that all the four lineages had populations with relatively stable over time and then subjected to sudden expansion during the late-Pleistocene era (c. 20 000 – 75 000 years ago). The phylogeographic and demographic history of C. nasus was highly influenced by climatic fluctuations in the Pleistocene. Geographic isolation resulted from Pleistocene climatic fluctuations might have profound impacts on the distribution pattern of genetic variation of C. nasus. Our result also indicated that the population expansion event for C. nasus occured along with habitat continuous expansion during the inter-glacial period.